Effects of salinity on pollutant removal and bacterial community in a partially saturated vertical flow constructed wetland. (June 2021) - Gao, Feng; Liu, Guochen; She, Zonglian; Ji, Junyuan; Gao, Mengchun; Zhao, Yangguo; Guo, Liang; Jin, Chunji
Graphical abstract: Highlights: Sufficient removal of pollutants was achieved despite the salinity varied. Removal of COD, NH4 + -N, TIN and TP occurred mainly within the unsaturated zone. Microbial community exhibited succession with salinity elevated. Unsaturated zone benefited the enrichment of functional group for nutrient removal. Abstract: This study investigated the influence of salinity on pollutant removal and bacterial community within a partially saturated vertical flow constructed wetland (PS-VFCW). High removal rates of NH4 + -N (88.29 ± 4.97–100 ± 0%), total inorganic nitrogen (TIN) (50.00 ± 7.21–62.81 ± 7.21%) and COD (91.08 ± 2.66–100 ± 0%) were achieved at 0.4–2.4% salinity levels. The removal of ammonia, TIN and organic matter occurred mainly in unsaturated zone. Salt-adaptable microbes became the dominant bacteria with salinity elevated. The proportion of ammonia-oxidizing bacteria (AOB) in the 0–5 cm depth layer (unsaturated zone) decreased obviously as the salinity increased to 2.4%. Nitrite-oxidizing bacteria (NOB) in the 0–5 cm depth layer showed a decreasing trend with elevated salinity. Denitrifying bacteria (DNB) in the 0–5 cm depth layer maintained high abundance (27.70–53.60%) at 0.4–2.4% salinity levels. At 2.4% salinity, AOB, NOB and DNB were observed in the unsaturated zones and saturated zones, and showed higher abundance in the unsaturated zone.